Isoform switching leads to downregulation of cytokine producing genes in estrogen receptor positive breast cancer - Khan, Mohammad Shahbaz; Hanif, Waqar; Alsakhen, Nada; Jabbar, Basit; Shamkh, Israa M.; Alsaiari, Ahad Amer; Almehmadi, Mazen; Alghamdi, Saad; Shakoori, Afnan; Al Farraj, Dunia A.; Almutairi, Saeedah Musaed; Hussein Issa Mohammed, Yasser; et al. (Frontiers in Genetics, 2023)
Estrogen receptor breast cancer is the most prevalent type of breast cancer, characterized by expression of estrogen receptors. It is the most common cancer among women with an incidence rate of 2.26 million cases worldwide. The aim of this study was to identify differentially expressed genes and isoform switching between estrogen receptor positive and triple negative breast cancer samples. For this study, the data was collected from ArrayExpress, followed by preprocessing and subsequent mapping from HISAT2. Read quantification was performed by StringTie and then R package ballgown was used to perform differential expression analysis. Functional enrichment analysis was conducted using EnrichR and then immune genes were shortlisted based on the ScType marker database. Furthermore isoform switch analysis was performed using isoformSwitchAnalyzeR package. A total of 9,771 differentially expressed genes were identified and among them 86 were upregulated and 117 were downregulated. Six genes were identified to be mainly associated with estrogen receptor positive breast cancer while a novel set of ten genes were found which have not been reported in estrogen receptor positive breast cancer previously. Moreover, alternative splicing and subsequent isoform usage in the immune system related genes were determined. This study identifies that differential usage of isoforms in the immune system related genes in cancer cells that suggest immunosuppression due to dysregulation of CXCR chemokine receptor binding, iron ion binding and cytokine activity.